Healthcare policy and urologic practice. Issue 4 (July 2017) - Pitts, Daniel; Sammon, Jesse D.
Abstract : Purpose of review: Healthcare policy is currently a topic of national debate, with numerous implications for the practice of urology. Recent findings: Healthcare policy has broad reaching effects, both predicted and unforeseen. The effects of healthcare policy are manifested through clinical practice guidelines, payment reform and the overall structure of the healthcare system. This review describes each of these topics and their impact on clinical practice, with a specific focus on urology and urologic practice. Summary: Guidelines are useful for guiding and determining what is considered appropriate clinical practice, but there are drawbacks including poor implementation and overabundance. Payment reform is constantly evolving, with multiple efforts being implemented to move away from a fee-for-service model of reimbursement. The structure of healthcare delivery is moving toward more outpatient procedures, with varying amount of physician ownership of facilities and equipment, which is itself a controversial topic.